Tribocorrosion in metal matrix composites - Toptan, Fatih; Rocha, Luís Augusto [UNESP] (My University, 2015)
One of the biggest motivations behind the development of the metal matrix composites (MMCs) is the improvement of the mechanical wear resistance of the unreinforced metallic matrix material mainly by the load-bearing effect of the hard reinforcement phases. However, in a large number of applications, MMCs are also required to operate in intimate contact with aqueous environments, which may lead to complex electrochemical phenomena that eventually may result in the degradation or pulling out of the reinforcement phases. Therefore, under these circumstances, MMCs may suffer a catastrophic degradation due to the joint action of electrochemical corrosion and mechanical wear (i.e. tribocorrosion), which is a multifaceted irreversible process where synergism or antagonism effects between the mechanical and electrochemical degradation phenomena may occur. Thus, this chapter aims to give an overview of the current knowledge of the mechanisms involved in the tribocorrosion degradation of MMCs and on the available testing procedures.